SUBSTANTIATION OF APPLICATION FEATURES OF LIQUID MIXTURES FOR SCREENING OF ELECTROMAGNETIC FIELDS: Array - Tykhenko, O. (Municipal economy of cities (Technical science), 2021)
The protective and rheological properties of composite materials based on water-dispersed paint and iron ore concentrate were studied. Features of liquid mixtures application for shielding of magnetic field of industrial frequency and electromagnetic field of ultrahigh frequency were substantiated. The study of the protective characteristics and rheological properties of composite materials based on water-dispersed paint and iron ore concentrate indicates the possibility of their use for shielding electromagnetic fields of a wide frequency range. It was found that the efficiency of the composite material (total shielding coefficient and reflection coefficient of electromagnetic waves) depends on the dispersion of the shielding filler, so the particle size analysis of iron ore concentrate was performed. The analysis shows that the predominant size of iron-containing particles is 23‒24 μm, which is quite acceptable for their uniform distribution in the body of the matrix. Shielding protective material was made of water-dispersion paint with the addition of iron ore concentrate in weight quantities of 15, 30, 45, 60%. The shielding coefficients of the electromagnetic field of industrial frequency and ultrahigh frequency with different filler content were measured. It was found that if the concentration of filler exceeds 30%, both the rheological characteristics of the mixture and the shielding coefficients of electromagnetic fields are unsatisfactory. A dramatic increase in shielding coefficients occurs at a filler concentration of 40%. This mixture has acceptable adhesive properties. It was established that the shielding coefficients could be enhanced if the dispersion of the filler is increased, which will contribute to the stability of the colloidal mixture and improve the rheological properties.